Neurocognitive Features of Mild Cognitive Impairment and Distress Symptoms in Older Adults Without Major Depression - Nantachai G; Maes M; Tran-Chi VL; Hemrungrojn S; Tunvirachaisakul C (Clinical Interventions in Aging, 2024)
Gallayaporn Nantachai,1– 3,* Michael Maes,1,2,4– 10,* Vinh-Long Tran-Chi,2,4 Solaphat Hemrungrojn,2,7 Chavit Tunvirachaisakul1,2,4,8 1Ph.D. Programme in Mental Health, Department of Psychiatry, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 2Department of Psychiatry, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 3Somdet Phra Sungharaj Nyanasumvara Geriatric Hospital, Department of Medical Services, Ministry of Public Health, Chon Buri Province, Thailand; 4Ph.D. Programme in Clinical Sciences, School of Global Health, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 5Sichuan Provincial Center for Mental Health, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 6Key Laboratory of Psychosomatic Medicine, Chinese Academy of Medical Sciences, Chengdu, People’s Republic of China; 7Cognitive Fitness and Biopsychiatry Technology Research Unit, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 8Center of Excellence in Cognitive Impairment and Dementia, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 9Research Institute, Medical University of Plovdiv, Plovdiv, Bulgaria; 10Department of Psychiatry, Medical University of Plovdiv, Plovdiv, Bulgaria*These authors contributed equally to this workCorrespondence: Michael Maes; Chavit Tunvirachaisakul, Email dr.michaelmaes@hotmail.com; Chavit.T@chula.ac.thBackground: Two distinct symptom dimensions were identified in older adults who did not have major depressive disorder (MDD): a) a dimension associated with mild cognitive dysfunction, and b) a dimension related to distress symptoms of old age (DSOA). It is uncertain whether previous findings regarding the features of amnestic mild cognitive impairment (aMCI) remain valid when patients with MDD are excluded.Methods: To examine the neurocognitive features of aMCI (n = 61) versus controls (n=59) and the objective cognitive characteristics of DSOA in participants without MDD. Neurocognition was evaluated utilizing the Cambridge Neurological Test Automated Battery (CANTAB) and memory tests.Results: This research demonstrated that CANTAB tests may differentiate between aMCI and controls. The One Touch Stockings of Cambridge, probability solved on first choice (OTS_PSFC), Rapid Visual Information Processing, A prime (RVP_ A´), and the Motor Screening Task, mean latency, were identified as the significant discriminatory CANTAB tests. 37.6% of the variance in the severity of aMCI was predicted by OTS_PSFC, RVP_ A´, word list recognition scores, and education years. Psychosocial stressors (adverse childhood experiences, negative life events), subjective feelings of cognitive impairment, and RVP, the probability of false alarm, account for 40.0% of the DSOA score.Discussion: When MDD is ruled out, aMCI is linked to deficits in attention, executive functions, and memory. Psychosocial stressors did not have a statistically significant impact on aMCI or its severity. Enhanced false alarm response bias coupled with heightened psychological stress (including subjective perceptions of cognitive decline) may contribute to an increase in DSOA among older adults.Keyswords: depression, mild cognitive impairment, adverse childhood experiences, stress, anxiety